Does Gen Z Care About CSR? The Mediating Role of Reputation in Driving Intention to Apply in a Competitive Labor Market - Aziz, Reyhan Abdul; Hakim, Abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Purpose – This study aims to examine the effect of corporate social responsibility (CSR) on Generation Z’s intention to apply for a job in Indonesia by investigating the mediating role of corporate reputation. Design/Methodology/Approach – This study employed a quantitative research design. Data were collected from 150 final-year students and fresh graduates in Indonesia selected through a purposive sampling technique. The data were gathered using an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings – The results indicate that CSR does not have a significant direct effect on Generation Z’s intention to apply for a job. Based on signaling theory, CSR signals may have low signal fit for applicants who prioritize financial stability. However, CSR has a positive and significant effect on corporate reputation, and corporate reputation fully mediates the relationship between CSR and job application intention. These findings suggest that CSR influences applicants’ intentions indirectly by strengthening perceptions of corporate reputation. Originality/Value – This study contributes to the employer branding and signaling theory literature by demonstrating that CSR alone is insufficient to attract Generation Z job applicants in a competitive labor market. Instead, the effectiveness of CSR depends on its ability to generate credible reputation signals. The findings provide practical implications for organizations in designing CSR strategies that strengthen corporate reputation and improve recruitment effectiveness.